Health-related quality of life, physical and mental capacity at one year follow up of COVID-19 ICU patients: A prospective cohort study - Anders Ersson; Henrik Överengen Reuterborg; Anestis Divanoglou; Richard Levi; Lotti Orwelius (Journal of Patient-Reported Outcomes)
Abstract Purpose In 2020 as COVID-19 rapidly overwhelmed ICU resources, patient care capacity was reduced thus increasing the risk of development of post intensive care syndrome (PICS). Therefore, an increased incidence of survivors with neurocognitive and neuromuscular impairment could be anticipated. This study aimed to describe residual reductions in health-related quality of life (HRQoL) and risk factors for PICS as they pertain to outcomes one year after intensive care. Patients and Methods Between 01-03-2020 and 31-08-2020, all adult COVID-19 ICU patients discharged alive in two Swedish ICU were included. At 2-, 6- and, 12-months post discharge follow up was conducted. Primary outcome parameters were HRQoL up to 12-months after ICU discharge. Secondary outcome parameters were clinimetric results for physical, mental, and cognitive functions at 6 months after intensive care stay. Results Data from 41 patients were analyzed. Fatigue, anxiety, respiratory impairments, and experienced decline in physical stamina were the dominating findings at 6 months. Criteria for PICS were fulfilled in 93% of the study population and a 60% reduction in overall HRQoL, compared with a normal age adjusted population, was seen at follow up. A slight improvement was seen at 6 months whereafter no further significant improvement in HRQoL was detected. Fatigue was the most dominant complaint, expressed by almost all patients at follow up. Conclusion Long term outcome reported in this study showed longstanding impairment in HRQoL, mostly related to reduced well-being and perceived limitations in physical ability. Overall, our findings show similarities with previously reported recovery patterns after intensive care. However, the COVID-19 cohort displayed a more profound reduction in HRQoL paralleled with severe fatigue and respiratory limitations. This signals the need for a deeper understanding of pathophysiological mechanisms of COVID-19 induced residual impairments and more precise instruments to tailor an individually designed aftercare.